Surgical treatment for infective endocarditis in the ageing society: a nationwide retrospective study in Japan - Hideo Yasunaga; Hiroyuki Morita; Taisuke Jo; Issei Komuro; Hiroyuki Kiriyama; Hidehiro Kaneko; Hidetaka Itoh; Tatsuya Kamon; Kojiro Morita; Katsuhito Fujiu; Masao Daimon; Norifumi Takeda (Open Heart)
Objective The current status of surgical treatment for infective endocarditis (IE) among very elderly people is unclear.Methods We extracted data on patients in Japan with community-acquired IE who were admitted and discharged between April 2010 and February 2018 using a nationwide inpatient, the Diagnosis Procedure Combination database. We divided patients into three groups: non-elderly (<65 years), elderly (65–79 years) and very elderly (≥80 years). A 1:1 propensity score matching was performed to compare proportions of surgical treatment and in-hospital mortality among the groups.Results We identified 20 667 eligible patients (median age 70 years, 61.0% men). The proportion of very elderly patients significantly increased (19.1% in 2010 to 29.7% in 2018). The proportion of surgical treatment was significantly lower, and in-hospital mortality was significantly higher in very elderly patients. This tendency was more pronounced among patients with in-hospital complications such as heart failure, stroke or embolism. Surgical treatment was significantly associated with lower in-hospital mortality even in very elderly patients, both in an unmatched (OR 0.61; 95% CI 0.47 to 0.78) and a propensity score matched cohort (OR 0.61; 95% CI 0.43 to 0.85).Conclusions The proportion of very elderly patients with IE was increasing, and very elderly patients had higher in-hospital mortality. The proportion of surgical treatment for IE among very elderly patients was low, but it was associated with lower in-hospital mortality. Further studies are needed to establish the optimal strategy for IE among very elderly patients.